1982
DOI: 10.3109/08860228209049850
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Peritonitis

Abstract: The development of cloudy peritoneal dialysis effluent is of great concern to the patient undergoing therapy with Continuous Ambulatory Peritoneal Dialysis. As described in this study, not all cloudy fluid represents bacterial infection. We describe the occurrence of cloudy fluid in eight patients in whom culture of the dialysate did not yield any growth, and whose cell count was characterized by the presence of significant numbers of the eosinophiles. As outlined, the entity of eosinophilic peritonitis has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…The differential cell count is characteristic in that there are <60% polymorphonuclear neutrophils and >10% eosinophils. Cultures for microorganisms do not yield any growth and tests for endotoxins are negative [3, 7, 8]. There is no history to suggest a global hypereosinophilic syndrome, allergic disease, parasitic infestation, polyserositis, immunodeficiency syndrome, tuberculosis, malignancy, or connective tissue disease.…”
Section: Clinical and Biological Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The differential cell count is characteristic in that there are <60% polymorphonuclear neutrophils and >10% eosinophils. Cultures for microorganisms do not yield any growth and tests for endotoxins are negative [3, 7, 8]. There is no history to suggest a global hypereosinophilic syndrome, allergic disease, parasitic infestation, polyserositis, immunodeficiency syndrome, tuberculosis, malignancy, or connective tissue disease.…”
Section: Clinical and Biological Featuresmentioning
confidence: 99%
“…The entity of peritoneal fluid eosinophilia has a characteristic presentation which allows for its distinction from more common bacterial peritonitis [8]. The classic presentation is a cloudy peritoneal fluid, present on an intermittent basis, and may not be seen with every bag exchange (table 1).…”
Section: Clinical and Biological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…48 There have been reports of non-bacterial, non-specific eosinophilic peritonitis in peritoneal dialysis patients. 49 There is usually an excellent prognosis with resolution within days, 50 although it can lead to encapsulating sclerosing peritonitis in recurrent cases. 51 The causative organisms in peritoneal dialysis peritonitis are generally different to those causing 'surgical peritonitis'.…”
Section: Peritoneal Dialysis Peritonitismentioning
confidence: 99%
“…Back in the early 1980s, it was reported that a certain proportion of patients developed a sterile peritonitis characterized by a predominance of eosinophils in the peritoneal dialysate within 3 months of the initiation of peritoneal dialysis (10)(11)(12). This type of peritonitis was termed eosinophilic peritonitis and was thought to be due to allergy to some constituents of the peritoneal dialysis system.…”
Section: Editorialmentioning
confidence: 99%